(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the linguistic and cultural representation of the concept of age in proverbs, focusing on the opposition between youth and old age in English and Uzbek paremiological traditions. Proverbs serve as an important means of reflecting the axiological worldview of a people, conveying life experience, cultural values, and moral guidelines. The study emphasizes that in English linguoculture, each stage of life — youth, maturity, and old age — has its own social function and significance. Special attention is given to the role of values and anti-values associated with different ages, which form the foundation of cultural identity and regulate human behavior. The analysis demonstrates that the concept of age in proverbs not only reflects everyday realities but also serves as a system of cultural orientation, transmitting ethical norms and life lessons from generation to generation.